2017
DOI: 10.7860/jcdr/2017/27073.10480
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Plasma Exchange - An Emerging Treatment Modality in Patients with Neurologic and Non-Neurologic Diseases

Abstract: Introduction: Therapeutic Plasma Exchange (TPE) is a procedure in which the patient's blood is passed through an apheresis machine, where the filtered plasma is removed and discarded with reinfusion of red blood cells along with replacement fluid such as plasma or albumin in to the patient. We present our experience with TPE in treatment of various neurologic and non-neurologic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 10 publications
1
38
0
2
Order By: Relevance
“…The effectiveness of TPE for treating acute onset of AIHA, for example, is only investigated in a small number of AIHA patients as reported by studies catalogued in English literature sources 7 . TPE is performed by filtration or centrifugation and removal of the plasma from blood using an apheresis machine, which is subsequently replaced with fluids such as fresh frozen donor plasma or albumin 15 . The use of TPE in AIHA has long been theorized to be effective as it can potentially remove hemolytic autoantibodies and activated complements proteins from circulation, thereby reducing the severity of the hemolytic reactions 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of TPE for treating acute onset of AIHA, for example, is only investigated in a small number of AIHA patients as reported by studies catalogued in English literature sources 7 . TPE is performed by filtration or centrifugation and removal of the plasma from blood using an apheresis machine, which is subsequently replaced with fluids such as fresh frozen donor plasma or albumin 15 . The use of TPE in AIHA has long been theorized to be effective as it can potentially remove hemolytic autoantibodies and activated complements proteins from circulation, thereby reducing the severity of the hemolytic reactions 16 .…”
Section: Introductionmentioning
confidence: 99%
“…7 TPE is performed by filtration or centrifugation and removal of the plasma from blood using an apheresis machine, which is subsequently replaced with fluids such as fresh frozen donor plasma or albumin. 15 The use of TPE in AIHA has long been theorized to be effective as it can potentially remove hemolytic autoantibodies and activated complements proteins from circulation, thereby reducing the severity of the hemolytic reactions. 16 Despite promising theories, previous case studies and observations have yielded conflicting results, with some claiming that TPE is able to significantly improve laboratory parameters and clinical symptoms, [17][18][19][20][21][22][23][24] some claiming that it is not effective in treating AIHA, 25 while others suggesting that TPE is only effective for cold AIHA.…”
Section: Introductionmentioning
confidence: 99%
“…TPE is an extracorporeal treatment that effectively removes antibodies, toxins, and immune complexes from the plasma and replaces it with another physiological fluid. TPE is to remove free hemoglobin substances from the plasma to allow the resolution of the disease and/or to decrease morbidity (5)(6)(7). TPE is also successfully used in patients having hemolytic anemia, regardless of immune or non-immune originated (8).…”
Section: Discussionmentioning
confidence: 99%
“…TPE is ideal for removal of toxic substances such as antibodies, toxins or abnormal proteins. Conditions such as Guillain-Barre syndrome, myasthenia gravis, monoclonal gammopathies, thrombotic thrombocytopenic purpura (TTP), hemolytic uremic syndrome, idiopathic thrombocytopenia, and rheumatologic diseases like systemic lupus erythematosus (SLE) have seen the use of TPE [3]. One volume exchange roughly removes plasma equivalent to 65% of the intravascular space.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse reactions from TPE can range from the more common reactions such as mild hypotension, fever, chills to rare life-threatening complications such as cardiovascular and respiratory compromise. The estimated overall incidence is around 9% with a range of 1.5%-25% [3,5]. Reports have shown that patients taking angiotensin-converting enzyme (ACE) inhibitors who undergo TPE, especially with albumin replacement are at an increased risk of serious reactions like sudden hypotensive episodes [6].…”
Section: Introductionmentioning
confidence: 99%